Penemuan Kandungan Asam Giberellin (GA3) pada Ekstrak Beberapa Jenis Tumbuhan - I NYOMAN GEDE ASTAWA; KHAMDAN KHALIMI (Agrotrop : Journal on Agriculture Science, 2023)
The Discovery of the Content of Giberellin Acid (GA3) in Extracts of Several Plant Spesies. Several studies have found that the application of growth regulator Giberellin can induce seedless in seeded varieties and also improve fruit quality in non-seeded varieties of grapes. It is also directly responsible for cell division and is used in horticulture to promote seed germination. The high price makes it unaffordable for farmers, especially in Indonesia, so it is necessary to look for other sources of GA3 which comes from extracts of plant species in Indonesia. The aims of this study were: To detect the content of gibberellin acid (GA3) in several plant species; The research was conducted at the Agronomy & Horticulture Laboratory, Faculty of Agriculture, Udayana University. The results of the study found that fresh corn kernels (Zea mays L.), young bamboo shoots (Bambusa sp.), fern leaves (Diplazium esculentum), spinach leaves (Amaranthus spp) and shallot bulbs (Allium cepa), contained as much as 215 µg GA3 mL-1, 257 µg GA3 mL-1, 260 µg GA3 mL-1, 154 µg GA3 mL-1 and 227 µg GA3 mL-1 respectively. It can be concluded that extracts of plant materials contain GA3 and can be used as a substitute for synthetic GA3.